(untitled) (Altre Modernità, 2021)
In 1978, the discovery in the Hornos de Lonquén - an abandoned mine in the metropolitan region of Santiago - of human remains belonging to men who had been detained in 1973 and had disappeared since then, confirmed suspicions of enforced disappearance by the Pinochet regime. This article analyses one of the elements of the impact of enforced disappearance on the victims’ relatives, friends and neighbours and on societies, focusing on Latin American cinema in whose narrative content the search for and eventual finding of the remains of disappeared detainees is of some relevance. We focus especially on three documentary films that show the importance of the Lonquén discovery in the Chilean imaginary and the strong symbolic value of Lonquén as a paradigm of a praxis of state violence and concealment of the truth that has caused immense trauma and has consequences nowadays.